A Quantitative Survey To Analyze The Impact Of Safety Gears To Prevent Lower Limb Injuries Among Taekwondo Trainees In Karachi, Pakistan - Samreen Iqbal; Daniya Shakir; Aimen Aijaz; Hareem Khan; Rabiya Arshad; Rumaisa Mazhar; Sabahat Nabi; Laraib Shaikh; Muhammad Uzair (Journal of Health, Wellness and Community Research, 2025)
Background: Taekwondo is a high-intensity martial art in which rapid kicking techniques and contact-based training expose young athletes to a substantial burden of lower-limb injuries, while routine use of protective equipment remains variable. Objective: To determine the prevalence and patterns of lower-limb injuries among taekwondo trainees in Karachi, Pakistan, and to evaluate safety gear use and its association with perceived injury prevention. Methods: A descriptive cross-sectional survey was conducted across five taekwondo academies in Karachi among trainees aged 12–20 years with 6–12 months of training experience. Data were collected using a structured injury reporting questionnaire capturing demographics, 12-month training-related lower-limb injuries (site, type, mechanism), 3-month muscle cramps, and routine protective equipment use. Data were analyzed in IBM SPSS version 24 using descriptive statistics and Fisher’s exact test. Results: Among 120 trainees (59.2% male), 52.5% reported at least one lower-limb injury in the past year. The most commonly injured sites were the foot (12.5%), lower leg (11.6%), and ankle (8.3). Bruises were most frequent (21.7%), followed by contusions and sprains (13.3% each); attack kicks (24.2%) and kick-blocking (15.8%) were leading mechanisms, while 44.2% reported no identifiable mechanism. Painful cramps occurred in 50.8% over the prior three months. Routine protective equipment use was reported by 43.3%. Protective equipment use was significantly associated with belief in injury-preventive benefit (p = 0.025). Conclusion: Lower-limb injuries and painful cramps are common among adolescent taekwondo trainees in Karachi, with injuries predominantly affecting distal lower extremity regions and arising from contact-based actions. Safety gear use was suboptimal but associated with stronger perceptions of preventive benefit, supporting the need for consistent protective practices and injury-prevention-focused training
Keywords: Taekwondo; Lower Limb Injuries; Protective Equipment; Musculoskeletal Injury; Injury Mechanism; Muscle Cramps; Injury Surveillance